Comparison between enzyme-linked immunospot assay and intracellular cytokine flow cytometry assay of cytomegalovirus-specific T-cell response in healthy participants - Chompunuch Klinmalai; Nopporn Apiwattanakul; Somsak Prasongtanakij; Jackrapong Bruminhent; Supanart Srisala (PLoS ONE, 2026)
Human cytomegalovirus (HCMV) usually establishes a lifelong latent infection after primary infection. Reactivation occurs sporadically and is controlled by cell-mediated immune response (CMIR). Monitoring of CMIR against CMV is mandatory in immunocompromised patients to adjust immunosuppressive drugs to prevent serious end-organ damage after CMV reactivation. Intracellular staining (ICS) and enzyme-linked immunospot (ELISPOT) quantifying CMV-specific T-cells are generally used as surrogate markers for CMIR against CMV. Whether the results of these 2 methods correlate well is not known. This study compared the numbers of CMV-specific T-cells identified by ELISPOT and ICS in healthy adult volunteers. Correlation with CMV serological status was explored. Thirty peripheral blood samples from healthy individuals were quantified for IFN-γ-producing cells after stimulation with whole CMV and IE1 using ICS, and IFN-γ-secreting cells after stimulation with whole CMV lysate and IE1 peptide pool using ICS and IFN-γ-secreting cells by ELISPOT. Anti-CMV IgG levels were analyzed concomitantly using a chemiluminescent microparticle immunoassay. There were 30 healthy participants, 15 (50%) male, with a mean age of 37.8 (± 7.6) years. Twenty-eight (93.3%) were seropositive against CMV. The CMV-specific CD3 + cells, as measured by ICS, were highly correlated with the spot numbers obtained by the ELISPOT, irrespective of CMV antigens used (whole CMV, r = 0.7677, p < 0.0001; IE1, r = 0.6516, p < 0.0001). The numbers of CMV-specific CD3 + cells quantified by IE1 stimulation by these 2 assays were statistically correlated with anti-CMV IgG levels (ICS, r = 0.5070, p = 0.004; ELISPOT, r = 0.4384, p = 0.015). Among the 30 participants, CMV-specific T cells were detected in all participants (100%), including the two seronegative individuals. The present study demonstrated that CMV-specific T-cells measured by ICS and ELISPOT assays were well correlated, suggesting that these assays could be used to monitor CMV-specific T-cells. CMV IgG levels may reflect prior CMV infection and CMV-specific cell-mediated immunity (CMIR) in immunocompetent individuals.